PENGARUH TEKNOLOGI INFORMASI, PENGETAHUAN PENGGUNA TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI - Fatyadi, Ahsan Mu’afi Fatyadi Mu’afi; Ramadhanti, Wita; Primasari, Dona (Soedirman Accounting, Auditing and Public Sector Journal, 2023)
The effectiveness of accounting information systems is needed for various types of businesses, which is in a minimarket. This study aims to determine the accounting information system that is influenced by information technology, user knowledge and moderated by task complexity. This research uses 70 samples taken from employees in the minimarket. Based on the results of research, information technology and user knowledge can influence accounting information systems. Meanwhile, task complexity cannot moderate the relationship between information technology and user knowledge with accounting information system.